Parameters of the knife-drum type device for separating sweet corn cobs - Papusha Sergey K.; Nikitenko Nikolay A.; Zhadko Valeria V. (E3S Web of Conferences, 2020)
The paper considers issues related to the application of the knife-drum type parameters design in order to increase the productivity of the maize harvesters in the phase of milk-wax ripeness. In this regard, energy-saving technologies are required. This device allows you to reduce the percentage of loss and injury of sweet corn grains due to the absence of pressure on the сob.